2016
DOI: 10.1001/jamacardio.2015.0292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Rheumatic Heart Disease in Eastern Nepal

Abstract: Rheumatic heart disease affects 1 in 100 schoolchildren in Eastern Nepal, is primarily clinically silent, and may be more common among girls. The overall prevalence and the ratio of manifest to subclinical disease increase with advancing age, whereas the incidence remains stable at 1.1 per 1000 children per year. Early detection of silent disease may help prevent progression to severe valvular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 23 publications
1
53
1
1
Order By: Relevance
“…2,3,4,5 In a school based cross sectional study in eastern Nepal, the prevalence of RHD (including subclinical) was found to be 10 per 1000 school children. 6 This study shows that subclinical RHD exist in large number in the community increasing the burden from RHD by several folds.…”
Section: Introductionmentioning
confidence: 71%
“…2,3,4,5 In a school based cross sectional study in eastern Nepal, the prevalence of RHD (including subclinical) was found to be 10 per 1000 school children. 6 This study shows that subclinical RHD exist in large number in the community increasing the burden from RHD by several folds.…”
Section: Introductionmentioning
confidence: 71%
“…11 Further we have observed that girls with RHD are slightly younger than boys, similar to observation made by Shrestha et al where RHD was commoner in girls and affecting them at a younger age. 3 The median duration of symptoms among new cases was 1 year (range, 1 week to 9 years) with one child had symptoms for as long as nine years without seeking any health care facilities. This signifies the delay in health seeking behavior and visiting the health facility only when the disease is severe which drastically increases the morbidity and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…4,8,9 Shrestha et al in their recent population based study in school going children of Eastern Nepal have reported an alarming prevalence of 10.2/1000 school children. 3 The mean age of children with RHD was 11.9 ± 2.2 years. This is consistent with the result from Nigeria where the mean age of children with RHD was recorded to be 10.8 ± 3.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two-thirds of the total number of students treated for pharyngitis were girls. There have been anecdotal reports that GAS pharyngitis is more common in females [27, 28], and several datasets demonstrate higher rates of ARF or RHD in females compared with males [8, 2932]. It is not understood if this pattern is due simply to sampling biases, differential access to health services by women and girls [31], increased risk of exposure to GAS (e.g., increased participation in childcare activities), increased biological risk for acquisition of GAS-related diseases, or other reasons [1].…”
Section: Discussionmentioning
confidence: 99%